Thermally Stable and High‐Mobility Dithienopyran‐Based Copolymers: How Donor–Acceptor‐ and Donor–Donor‐Type Structures Differ in Thin‐Film Transistors. Issue 8 (22nd June 2021) - Jeong, Seonghun; Yoo, Hyeonjin; Cho, Yongjoon; Yoon, Seong-Jun; Lee, Byoung Hoon; Yang, Changduk
Abstract : Although rapid and remarkable progress has been made in semiconducting polymers used in organic field‐effect transistors (OFETs), the development of novel π‐conjugated backbones remains the central issue in this field. High FET mobilities have been achieved for copolymers based on fused‐ring building blocks due to their strong tendency to form ππ stacks. However, introducing the recently formulated strong electron‐rich fused‐ring dithienopyran (DTP) unit in the polymer backbone has garnered considerably less attention. Herein, four new copolymers (donor–acceptor (DA)‐type versus donor–donor (DD)‐type structures) are synthesized based on the DTP unit by adopting different types of counterparts of the backbone. The characteristics of these copolymers, derived from different structural types, are investigated and compared and they are implemented in OFET devices. The DA‐type copolymers (P1 and P2) show higher charge‐carrier mobilities and better thermal stability than the DD‐type copolymers (P3 and P4), attributed to enhanced crystalline features induced by strong intermolecular interactions and preferential 3D‐textured molecular orientation of the DA‐type copolymers. Particularly, P1 exhibits the highest mobility of up to 0.22 cm 2  V −1  s −1 . This study provides a reference for understanding the influence of the backbone type on the structure–property relation and promotes the development of high‐performance DTP‐based copolymers. Abstract : Four dithienopyran (DTP)‐based copolymers are designed and synthesized by applying the DTP unit with either electron‐accepting or electron‐donating units. Their characteristics derived from the structural type are systemically investigated, and they are utilized in organic field‐effect‐transistor devices. As a result, donor–acceptor‐type copolymers exhibit higher charge‐carrier mobility with better thermal stability than donor–donor‐type copolymers.